Diagnostic value of computed tomography, radiography and ultrasonography in metacarpophalangeal joint disorders in horses - Machado, V. M V [UNESP]; Aguiar, A. C S [UNESP]; Viana, G. F. [UNESP]; Crosignani, N. O. [UNESP]; Filho, J.N.P. Puoli [UNESP] (FapUNIFESP (SciELO), 2016)
In modern society the work and athletic performance of horses has led to a very important animal production sector in which Brazil possesses the third largest horse stock. Among all equine lesions described, metacarpophalangeal (fetlock) joint lesions are considered one of the main causes of lameness. Consequently, there is a need to improve the understanding and diagnosis of these injuries. The most efficient imaging diagnostic methods for the fetlock region are computed tomography, radiography and ultrasound. Imaging studies of the anatomical structures involving this joint are extremely important to obtain a more precise diagnose. The present study was performed in order to evaluate the capacity of different imaging diagnostic modalities to detect a variety of lesions in different fetlock structures. Twenty horses (Equus caballus) used for horsemanship activities were referred to the Department of Animal Reproduction and Veterinary Radiology of São Paulo State University, Botucatu campus, with clinical signs of metacarpophalangeal joint injuries. Horses were submitted to radiographic and ultrasonographic exam and computed tomography scan. Image analysis revealed a significant capacity of these methods to characterize lesions in this region. However, computed tomography provided broader and better evaluation of lesions in bones and adjacent structures, because it allows the analysis to be performed on three-dimensional projections, with attenuation coefficients (window selections) and tissue density measurement through Hounsfield Units (HU).
Keywords: Computed tomography; Horses; Metacarpophalangeal joint; Radiography; Ultrasonography